Analisis Persepsi dan Ekspektasi Mahasiswa atas Kualitas Dosen Pembimbing Tesis di program Magister Akuntansi FEB Universitas Sam Ratulangi Manado - Lambey, Linda; Lambey, Robert; Kalangi, Lintje (Universitas Sam Ratulangi, 2017)
Abstract. One of the requirements to graduate from Magister of Accounting program at the Faculty of Business and Economics, Univevrsity of Sam Ratulangi Manado is to write thesis. Thesis supervisors are crucial for student’s successful of their thesis completion. This study aims to analyse student’s perceptions and expectations on their thesis supervision. This research contributes to practical and theoretical implications. In terms of practical implication, it is intended to help the management in providing advices and suggestions to thesis supervisors. Thus, thesis supervisors can provide their services and or supervisions in the ways to satisfy their students’ expectations. The theoretical implication is to contribute perception and expectancy theories in the higher education setting between student and academic. This is a qualitative exploratory research. Data were collected by conducting in-depth interviews to 12 respondents who graduated from the program, observation and documentation. Data were analysed by content analysis. Findings suggested that supervisors are expected to be excellent in research methods, experienced and senior, have published their international publications, excellent in information technology, know the research topic, can give great directions towards their students, and can be thesis proofreaders. On the other hand, supervisors are perceived as qualified thesis supervisors if those academics can spend their time sufficiently with their students, have close and emotional relationships with their students, can explain, give directions and communicate effectively with their students and finally, they can write excellent research. Keywords: Perception, expectancy, qualifications of thesis supervisors Abstrak. Salah satu syarat kelulusan mahasiswa program Magister Akuntansi (MAKSI) di Fakultas Ekonomi dan Bisnis Universitas Sam Ratulangi Manado adalah menyelesaikan tesis atau karya ilmiah akhir. Kualitas dosen pembimbing amat berperan terhadap keberhasilan penulisan tesis ini. Untuk itu, tujuan penelitian ini adalah untuk menganalisis persepsi dan ekspektasi mahasiswa terhadap kualitas dosen pembimbing tesis mereka. Penelitian ini diharapkan dapat memberikan kontribusi praktis bagi penyelenggara program untuk mengarahkan dosen dalam menyelenggarakan pembimbingan yang dapat memberikan kepuasan bagi para mahasiswa. Sedangkan manfaat teoritis dari penelitian ini adalah untuk memberikan kontribusi literature terhadap teori persepsi dan ekspektasi di dunia pendidikan tinggi. Penelitian ini dilakukan dengan menggunakan exploratory qualitative research dengan jumlah responden sebanyak 12 orang mahasiswa yang telah menyelesaikan studi mereka di program MAKSI ini. Data dianalisa dengan menggunakan content analysis dan dikumpulkan melalui in-depth interviews, observation dan documentation. Hasil penelitian menunjukkan bahwa dosen pembimbing tesis dikatakan berkualitas jika dosen tersebut menguasai metode penelitian, dosen senior yang sudah berpengalaman, dosen yang sudah memiliki publikasi/jurnal internasional, dosen yang menguasai aplikasi komputer, dosen yang menguasai materi/topik tesis yang dibimbing, dosen yang dapat mengarahkan mahasiswa dan dosen yang memiliki ketelitian dalam membaca atau memeriksa tesis mahasiswa. Sedangkan persepsi mahasiswa atas kualitas dosen pembimbing yang diinginkan oleh mahasiswa adalah dosen yang dapat meluangkan waktu yang cukup untuk pembimbingan, dosen yang bisa memiliki kedekatan emosional dengan mahasiswa bimbingannya, dosen yang mampu menjelaskan, mengarahkan dan berkomunikasi dengan efektif dan dosen yang mampu membuat penelitian yang berkualitas.Kata kunci: Persepsi, Ekspektasi, Kualitas Dosen Pembimbing Tesis.